Exercise endurance-training alters vitamin E tissue levels and red-blood-cell hemolysis in rodents. Issue 3 (March 1984) - Aikawa, K. M.; Quintanilha, A. T.; de Lumen, B. O.; Brooks, G. A.; Packer, L.
Abstract : Muscle tissue levels of dl-α-tocopherol (vitamin E) were significantly lower in endurance-trained rats than in sedentary animals, whether the animals were fed on vitamin-E-deficient or control (vitamin-E-sufficient) diets. In vitamin-E-deficient rats, liver tissue levels of vitamin E were significantly lower in those that were endurance-trained than in those that were sedentary; this was not the case in control animals. In addition, for vitamin-E-deficient rats, the onset of red-blood-cell hemolysis in the sedentary animals occurred one week earlier than in the endurance-trained animals. Thus, it appears that training induces a protective effect against hemolysis despite vitamin E deficiency.